2023
DOI: 10.1038/s41467-023-40226-9
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and complex drought effects on vegetation physiology inferred from space

Abstract: The response of vegetation physiology to drought at large spatial scales is poorly understood due to a lack of direct observations. Here, we study vegetation drought responses related to photosynthesis, evaporation, and vegetation water content using remotely sensed data, and we isolate physiological responses using a machine learning technique. We find that vegetation functional decreases are largely driven by the downregulation of vegetation physiology such as stomatal conductance and light use efficiency, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Flash droughts within a month and seasonal droughts longer than a month coexisted in the study area. (2) The DSSAT−CANEGRO model has a good simulation accuracy concerning the response of sugarcane growth to multiple meteorological drought scenarios in Lai-bin. The greater the intensity and the longer the duration of historical meteorological drought, the stronger the inhibition on the CY, SH, LAI, and ET of sugarcane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flash droughts within a month and seasonal droughts longer than a month coexisted in the study area. (2) The DSSAT−CANEGRO model has a good simulation accuracy concerning the response of sugarcane growth to multiple meteorological drought scenarios in Lai-bin. The greater the intensity and the longer the duration of historical meteorological drought, the stronger the inhibition on the CY, SH, LAI, and ET of sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…The formation and evolution mechanism of drought is very complicated, and its influence is also extremely extensive. In recent years, climate change has increased the risk and severity of drought in most parts of the world, with more prominent and complex impacts on agriculture, especially for the crop growth process and yield accumulation [1,2]. Furthermore, the influence mechanism has the characteristics of multi-stage chain transmission from meteorological drought to soil drought, and then to the physiological and ecological response of crops [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…When explaining the recovery rate, we selected characteristics of the flash drought, including speeds, severity, and duration, as well as the physiological characteristics of vegetation-the decline rate of vegetation productivity upon exposure to flash drought. We trained a random forest model and used these considered variables as predictive factors to estimate the productivity recovery rates, respectively, across all studied grid cells (Li et al 2023). We evaluated the model's sufficiency in explaining the productivity recovery rates by out-of-bag.…”
Section: Attribution Analysismentioning
confidence: 99%
“…Studies have shown that changes in vegetation were significantly and positively correlated with drought changes in nearly 54% of global vegetated lands, as well as in approximately 71% of the total area of China [16,17]. Drought affected vegetation mainly through the induction of plant water stress, which resulted in negative impacts on vegetation growth and metabolism, ultimately leading to a slowing of vegetation growth and even the mortality of vegetation [18,19]. Over the TP, some researchers have indicated that the intensity, duration, and frequency of droughts in the TP have shown an upward trend over the past few years [20,21].…”
Section: Introductionmentioning
confidence: 99%